Religion in the Metaverse Scheme: Practices of Worship in the New Media Age - Fernando, Henky; Larasati, Yuniar Galuh; Barkah, Qodariah; Andriyani; Morin, Leanne (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
The simulation of religious practices within the metaverse represents a new phenomenon in the discourse of religion and technological adaptation in the era of new media. Through the use of virtual reality technology, spiritual experiences can be presented in immersive forms within digital spaces. However, this phenomenon remains underexplored in existing academic studies. This research aims to address that gap by analyzing the discourse surrounding the simulation of religious practices in the metaverse through a contextual interpretation of Muslim perspectives. The study employs a qualitative descriptive method with a case study approach. The findings indicate that the simulation of worship in the metaverse is generally accepted by Muslims as a form of technological adaptation, functioning as a tool for education and the dissemination of religious knowledge, as long as it does not compromise the theological meaning or orientation of religious practices. The significance of this study lies in its contribution to building a reflective framework for understanding the interplay between religion and technological adaptation in the new media age.